Integrating New Technologies for Striga Control 2007
DOI: 10.1142/9789812771506_0006
|View full text |Cite
|
Sign up to set email alerts
|

GENETIC DIVERSITY OF STRIGA AND IMPLICATIONS FOR CONTROL AND MODELING FUTURE DISTRIBUTIONS

Abstract: The current knowledge of genetic diversity of Striga asiatica, S. hermonthica, and S. gesnerioides is reviewed. The genetic variability of these species has not been sufficiently evaluated relative to their wide distributions. Genetic diversity is a result of hybridization, clinal variation, local adaptation, and frequent colonization events. Colonization events of autogamous species formed genetically uniform populations. There is a general correlation between geographic distance and genetic distance and evid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 25 publications
1
26
0
Order By: Relevance
“…Limited studies on witchweed genetic diversity have been conducted, especially considering its wide range (Mohamed et al 2007). Striga hermonthica is an obligate outbreeder (Safa et al 1984), and its hybridization with Striga aspera has caused some taxonomic confusion (Aigbokhan et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Limited studies on witchweed genetic diversity have been conducted, especially considering its wide range (Mohamed et al 2007). Striga hermonthica is an obligate outbreeder (Safa et al 1984), and its hybridization with Striga aspera has caused some taxonomic confusion (Aigbokhan et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Mohamed et al (2007) have listed geographic isolation as a significant evolutionary force shaping the genetic structure of S. hermonthica populations. Some diversity assessment studies using allozymes and random amplified polymorphic DNA demonstrated that geographic distance played a major role in determining the genetic differentiation in S. hermonthica populations collected from different countries in the various regions of Africa (Bharathalakshmi et al, 1990; Kuiper et al, 1996; Koyama, 2000).…”
mentioning
confidence: 99%
“…The observation confirms the findings by Press and Phoenix (2005) that most parasitic plants can potentially attack a large number of differently occurring species hence they have been called 'generalists' although there are exceptions to that assertion. Mohamed et al (2007) also reported that Striga spp have been found parasitizing cereals crops and wild plants. The implications of this observation is that rotation can no longer be effective as the parasite can still depend on the weed for survival until seed production.…”
Section: Parasites and Their Hostsmentioning
confidence: 96%